Combination Of Riluzole And Rivastigmine- A Potential Treatment Strategy For Alzheimer’s Disease - Chintha Narendar; M Tharani; Gaddam Narasimha Rao; M Anvesh Raj; Antony Justin (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
To fulfill clinical needs, it is essential to deploy viable treatment techniques for Alzheimer's disease (AD). The development of potential therapeutic drugs for the treatment of Alzheimer's disease in the early stages and the optimization of symptomatic treatment are top priorities in AD research. Recently multitarget therapies are gaining a lot of interest due to their potential advantages. The current review aims to review the advantages of combined targeting of Cholinesterase inhibitors (ChEIs) and Nmethyl D-aspartate (NMDA) antagonists in the treatment of AD. In order to evaluate the all-possible aspects of ChEIs and NMDA antagonists in the treatment of AD, we have examined documentation available in published literature. Recently, Riluzole has been approved for amyotrophic lateral sclerosis (ALS), and rivastigmine for Alzheimer's disease. A recent study suggested that Riluzole may show therapeutic benefits in the treatment of AD. As, Rivastigmine is an existing therapy for mild to moderate AD, drugs that act for severe AD are necessary. So, combination therapy (CT) with Riluzole and rivastigmine may act as a potential treatment strategy for AD is beneficial. When compared with monotherapy, the combination approach simplifies the treatment regimen and increases patient compliance. For sufferers with excessive AD, CT with ChEIs and NMDA antagonists seems to be the simplest and most powerful therapy.